2012
DOI: 10.1016/j.neuron.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Memory: Remembering, Imagining, and the Brain

Abstract: During the past few years, there has been a dramatic increase in research examining the role of memory in imagination and future thinking. This work has revealed striking similarities between remembering the past and imagining or simulating the future, including the finding that a common brain network underlies both memory and imagination. Here we discuss a number of key points that have emerged during recent years, focusing in particular on the importance of distinguishing between temporal and non-temporal fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
932
3
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,191 publications
(997 citation statements)
references
References 213 publications
(357 reference statements)
55
932
3
7
Order By: Relevance
“…Findings from cognitive, neuropsychological, and neuroimaging research have shown that episodic future thoughts are created based on informational components provided by episodic and semantic memory (i.e., specific past experiences and general knowledge about the world and the self), and multiple cognitive processes are engaged to retrieve, select, and assemble relevant pieces of information (for reviews, see D 'Argembeau, 2015;Irish & Piguet, 2013;Klein, 2013;Schacter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from cognitive, neuropsychological, and neuroimaging research have shown that episodic future thoughts are created based on informational components provided by episodic and semantic memory (i.e., specific past experiences and general knowledge about the world and the self), and multiple cognitive processes are engaged to retrieve, select, and assemble relevant pieces of information (for reviews, see D 'Argembeau, 2015;Irish & Piguet, 2013;Klein, 2013;Schacter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the neuroimaging studies in healthy subjects, a striking overlap between the functional underpinnings of remembering the past and imagining the future has been observed. The mental time travel brain network, showing an extended overlap with the default network, encompasses the medial frontal and temporal regions, posterior and retrosplenial cortex, lateral parietal and temporal regions (see Schacter et al 2012 for a review). Despite the fact that these investigations have demonstrated similarities in terms of AM and EFT neurocognitive mechanisms, some differences have also been documented.…”
mentioning
confidence: 99%
“…This network acquired the name ‘default mode network’83 because it was active in subjects in fMRI experiments when they were not engaged in attention‐demanding goal‐directed cognitive challenges. The network might be better named the actor–scene or scenario network, since it supports not only autobiographical recall but also thinking about the minds and personalities71 of others, as well as future scenes84 involving self and others 78, 79, 80, 85, 86, 87. Much of the cognitive neuroscientific research on this network has focused on autobiographical memory and imagination,88 on constructive episodic memory as the basis for future episodic simulation (‘the ability to flexibly recombine elements of past experience into simulations of novel future events’),78, 85, 86, 89 and on the social imagination engaged in fiction 90, 91, 92.…”
Section: Evolving In the Narrative Nichementioning
confidence: 99%